(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the situation of routine hand-hygiene compliance by hospital staff and some associated factors at Son La Provincial General Hospital in 2022. Methods: A cross-sectional study was conducted with a sample size of 350 hospital staff. Results: The proportion of compliance with routine hand-hygiene of the medical staff at the hospital accounted for 60.6%. There was a correlation between participation in infection control training (OR=0.66; 95% CI: 0.5-0.9; p<0.05), and patient overload at the ward (OR=1.57; 95% CI: 1.3- 1.9; p<0.05), process inspection and monitoring (OR= 0.67; 95% CI: 0.5-0.9; p<0.05), knowledge of hand-hygiene compliance (OR = 0.77; 95% CI: 0.6 - 0.9; p <0.05) to compliance with routine handhygiene.